Acrylic resin removable partial overdenture with bare root on extruded 45 - Rosa Sharon Suhono; Endang Wahyuningtyas; Titik Ismiyati; Heriyanti Amalia Kusuma (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2017)
Bare root overdenture is a denture supported by a dome-shaped endodontic treated teeth with height 2-3 mm above the gingival surface. All prepared area of 45 was filled with composite material. The abutment teeth resisted the alveolar bone resorption process and maintains the height of alveolar crest, in order to support the retention and stability of removable partial denture (RPD). The aim of this case study was to investigate the treatment of acrylic resin RPD with bare root overdenture on extrusion tooth 45. A 54 years old male patient with loss of teeth 18, 17, 15, 14, 22, 23, 24, 26, 27, 28, 38, 37, 36, 35, 32, 31, 44, 46 was presented in Prof. Soedomo Dental Hospital Faculty of Dentistry, Universitas Gadjah Mada, Yogyakarta.Tooth 45 was extruded thus promoted locked occlusion. This case management was comprised of anamnesis, clinical examination, study model impression, design of RPD with bare root overdenture on tooth 45, endodontic treatment, dome-shaped preparation, filling with composites material cover the entire surface of prepared tooth 45, working model impression, determination of maxilla-mandibular relation, artificial teeth arrangement, try-in denture, insertion, and control. Evaluation after insertion showed good retention and stability, established good occlusion and satisfied aesthetic by using the RPD with bare root overdenture on tooth 45. At control appointment, patients described comfortable feeling because the use of bare root overdenture could maintain the denture stability and retention, and there was no locked occlusion when RPD was used. In this reported case, the RPD with bare root overdenture on extruded 45 repaired occlusion and aesthetic of patient and did not lock the occlusion. ABSTRAKBare root overdenture adalah gigi tiruan yang didukung oleh gigi yang telah dirawat endodontik dan dipreparasi dengan bentuk dome-shaped setinggi 2-3 mm di atas permukaan gingival serta dilakukan penambalan komposit menutupi seluruh area yang dipreparasi. Adanya gigi pendukung dapat menghambat proses resorpsi tulang alveolar dan tinggi processus alveolaris dapat dipertahankan dalam menunjang retensi dan stabilitas gigi tiruan lepasan. Laporan kasus ini bertujuan untuk mengkaji perawatan gigi tiruan sebagian lepasan (GTSL) resin akrilik dengan penyangga bare root pada gigi 45 ekstrusi. Pasien laki-laki berusia 54 tahun dengan kehilangan gigi 18, 17, 15, 14, 22, 23, 24, 26, 27, 28, 38, 37, 36, 35, 32, 31, 44, 46 datang ke Rumah Sakit Gigi dan Mulut Prof. Soedomo Fakultas Kedokteran Gigi, Universitas Gadjah Mada, Yogyakarta. Gigi 45 ekstrusi, sehingga mengakibatkan oklusi terkunci. Penatalaksanaanpasien dilakukan sebagai berikut: anamnesa, pemeriksaan klinis, perawatan endodontik dan preparasi serta penambalan dengan komposit pada gigi 45, pembuatan desain GTSL resin akrilik dengan penyangga bare root gigi 45, pencetakan model kerja, menentukan relasi maksila – mandibula, penyusunan gigi, percobaan protesa malam, insersi, dan kontrol. Insersi menunjukkan retensi, stabilisasi, oklusi, dan estetis baik pada GTSL dengan bare root gigi 45.Hasil kontrol menunjukkan pasien merasa nyaman kerena penggunaan bare root overdenture dapat mempertahankan stabilitas gigi tiruan dan oklusi tidak terkunci saat GTSL berfungsi. Dari kasus yang dilaporkan dapat disimpulkan GTSL dengan penyangga bare root pada gigi 45 ekstrusi dapat memperbaiki fungsi oklusi dan estetis yang baik, serta tidak mengakibatkan oklusi terkunci.